PENGARUH KOMPOSISI AMELIORAN TERHADAP PERTUMBUHAN DAN HASIL DUA VARIETAS KUBIS BUNGA PADA LAHAN PASANG SURUT SULFAT MASAM DENGAN SISTEM BUDIDAYA JENUH AIR - Nurjani, Nurjani; Basuni, Basuni; Wasian, Wasian; Zulfita, Dwi (Fakultas Pertanian, Universitas Janabadra, 2024)
The development of tidal land for agriculture faces various challenges in order to provide high productivity. One of the plant cultivation techniques developed in tidal areas is water saturated cultivation. This research aims to determine the growth and yield of flowering cabbage in acid sulphate tidal fields using a water-saturated cultivation system applied with various amelioran compositions. This research was carried out in Kalimas village, Sungai Kakap District, Kubu Raya Regency for 8 months (April – October). The research design that will be used is a field experiment with a split plot design with 2 treatment factors and 3 replications. The main plot is the Flower Cabbage variety (K) which consists of 2 varieties: k1 = Larissa F1 and k2 = Snow White F1. As a subplot is the amelioran composition (A) which consists of chicken manure (pka), goat manure (pkk), biological fertilizer (ph) and dolomite lime (kd) with 8 compositions, namely: a1 = pka, a2 = pkk, a3 = pka + ph a4 = pkk + ph, a5 = pka + kd, a6 = pkk + kd, a7 = pka + ph + kd, and a8 = pkk + ph + kd. The results of the research show that the amelioran composition has the same effect, while the variety and depth of the water table have a different effect on the growth of flowering cabbage plants on acid sulfate tidal land with a water-saturated cultivation system. The Larissa variety provides better growth than the Snowhite variety.